IMPACT OF SOCIAL NETWORKING SITES ON THE YOUTH OF INDIA - Shina, Pankaj Kumar (International Journal of Research Science and Management, 2015)
The impact of social networking sites can be superior for students but if we have a closer look on these social networking sites . Today it is sullying the future and carrier of students. The social networking websites like facebook.com, twitter.com, orkut , etc. are incessantly disturbing students from their studies. The main meeting point of student should be education but unluckily today’s student are emphasizing on such networking sites which can be a complete expenditure of time